1992
DOI: 10.1088/0031-9155/37/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Water-equivalent plastic scintillation detectors for high-energy beam dosimetry: I. Physical characteristics and theoretical considerations

Abstract: A minimally perturbing plastic scintillation detector has been developed for the dosimetry of high-energy beams in radiotherapy. The detector system consists of two identical parallel sets of radiation-resistant optical fibre bundles, each connected to independent photomultiplier tubes (PMTs). One fibre bundle is connected to a miniature water equivalent plastic scintillator and so scintillation as well as Cerenkov light generated in the fibres is detected at its PMT. The other 'background' bundle is not conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
432
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(442 citation statements)
references
References 14 publications
7
432
1
2
Order By: Relevance
“…Beddar et al 4. showed that when a plastic scintillating fiber attached to a photomultiplier tube was exposed to a photon beam, it exhibited high sensitivity, a linear dose – response, a fast response to ionizing radiation and low angular dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Beddar et al 4. showed that when a plastic scintillating fiber attached to a photomultiplier tube was exposed to a photon beam, it exhibited high sensitivity, a linear dose – response, a fast response to ionizing radiation and low angular dependence.…”
Section: Introductionmentioning
confidence: 99%
“…The air core FOD is a cylindrical scintillation dosimeter with a sensitive volume of 1 mm diameter and 1 mm length, manufactured for use in external beam dosimetry, has been shown to be dosimetrically water‐equivalent, have no directional dependence, and have sufficient spatial resolution for use in field sizes as small as 4 mm in diameter 10 , 19 , 21 . Scintillation dosimeters are a good choice as a reference detector for small field work 15 , 22 as their response has been shown to be independent of dose rate, energy, and temperature, and they provide a linear response with delivered dose 23 , 24 . Scintillation dosimeters have been benchmarked against film 10 , 21 and Monte Carlo (25) and have a smaller measurement uncertainty than film.…”
Section: Methodsmentioning
confidence: 99%
“…9,14 Owing to their water equivalence and good spatial resolution, plastic scintillation detectors (PSDs) could play an important role in small-field dosimetry. Several authors have studied PSDs in recent years: 10,[15][16][17][18][19][20] their linear response to absorbed dose, dose rate and energy independence are well known. Consequently, PSDs have just found large application in small-field dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The main drawback of plastic scintillators is represented by the generation ofČerenkov light in the optical fibre guide when the scintillator is exposed to a radiation field. Two main approaches have been suggested to subtract thě Cerenkov light component: the method proposed by Beddar et al, 15,16 which uses a background optical fibre not coupled with a scintillating fibre, and the two-fibre or spectral method, proposed by Fontbonne et al 25 and reformulated by Guillot et al, 26 which is based on the dependence of the intensity of thě Cerenkov light on the length of the exposed fibre and measures the light signal by means of two different wavelength channels. Morin 22 has proposed a modification of the measurement procedure proposed by Guillot et al 26 to determine the Cerenkov spectrum with the detector placed with the stem parallel to the beam axis.…”
Section: Introductionmentioning
confidence: 99%